(untitled) (Research, Society and Development, 2024)
Autistic Spectrum Disorder (ASD) or Autistic Disorder (ED), popularly known as autism, is characterized by being a syndrome that interferes with the child’s neurodevelopment. Objective: To analyze the nursing care intervention for children with ASD in the literature. El Trastorno del Espectro Autista (TEA) o Trastorno Autista (TCA), conocido popularmente como autismo, se caracteriza por ser un síndrome que interfiere en el neurodesarrollo del niño. Objetivo: Analizar la intervención de cuidados de enfermería para niños con TEA en la literatura. Methodology: This is a narrative review of literature with a qualitative and exploratory approach. Databases were used on the platforms. Latin American and Caribbean Health Sciences Literature (LILACS) via the Virtual Health Library (VHL) and the Online System for Search and Analysis of Medical Literature (MEDLINE) via PubMed. Determining the period from 2020 to 2024. Results: 35 publications were found, after submitting to the inclusion and exclusion criteria, 20 publications that are part of this study were identified. Final considerations: nursing care involves a therapeutic project, with specific therapies. This summary of the authors’ discussions contributes to the knowledge of the various specificities of care that the health professional assists the child with ASD. It is necessary to have the ability to train and take action with new methods of care, both in health care and in clinical practice. In their studies, the authors emphasize the difficulty of nurses in clinical practices.